Overview of Learning Motivation and Learning Strategies of Students In The Medical Study Program - Sholahuddin Tumanggor; Hasna Dewi; Patrick William Gading; Rina Nofri Enis; Nyimas Natasha Ayu Shafira (Journal of Medical Studies, 2024)
ABSTRACT Background: Medical education is not easy and requires concentration and a strong will to be able to complete all stages of education. Students must have strong motivation and learning strategies that are considered to have contributed to the success of the learning process because of a lack of motivation and strategy in learning. With that, motivation and learning strategies influence a person's activities to achieve the results he wants. Method: This research is included in the category of associative research using a quantitative approach. The sample is 285 undergraduate students of the Medical Education Study Program at the Faculty of Medicine and Health Sciences active in the odd semester of the 2022/2023 academic year. The data analysis technique used is univariate analysis. Results: The results show that 75.5% of students from the class of 2020 have moderate learning motivation, 86.6% of students from the class of 2021 have moderate learning motivation, 72.8% of the class of 2020 students have moderate learning strategies, and 90.3% of the class of 2021 students have moderate learning strategies. Conclusion: Most of the 2020 and 2021 active Medical Education Study Program undergraduate students at the Faculty of Medicine and Health Sciences in the odd semester of the 2022/2023 academic year have moderate motivation and learning strategies. Keywords: learning motivation; learning strategy; medical student